The mediating role of emotional intelligence between self-efficacy and resilience in Chinese secondary vocational students - Ruichen Jiang; Ruichen Jiang; Ruichen Jiang (Frontiers in Psychiatry, 2024)
PurposeThis study aimed to explore the relationship between self-efficacy and resilience in Chinese secondary vocational students and examine the mediating effect of emotional intelligence.MethodsIn September 2023, a cross-sectional survey was conducted in 282 Chinese students from three secondary vocational schools by using a voluntary and anonymous structured questionnaire, which included a general self-efficacy scale (GSES), emotional intelligence scale (EIS), and resilience scale (RS). The data were analyzed using SPSS 26.0 software and macro PROCESS.ResultsThe scores of self-efficacy, emotional intelligence, and resilience of Chinese secondary vocational students were above the average level. Correlations among the self-efficacy, emotional intelligence, and resilience levels of students were significant. The analyses of mediating effect showed that emotional intelligence partially mediated the influence of self-efficacy on resilience of secondary vocational students.ConclusionSelf-efficacy was positively associated with resilience. Self-efficacy not only has a direct effect on the resilience of secondary vocational students but it also indirectly affects the resilience through the mediating role of emotional intelligence. These findings valuable for designing the secondary vocational school programs aimed at improving students’ psychological resilience.